2011
DOI: 10.1038/bjc.2011.500
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the expression of EEF1A1/2 genes in human prostate cancer cells: the potential of EEF1A2 as a hallmark for prostate transformation and progression

Abstract: Background:In prostate adenocarcinoma, the dissection of the expression behaviour of the eukaryotic elongation factors (eEF1A1/2) has not yet fully elucidated.Methods:The EEF1A1/A2 expressions were investigated by real-time PCR, western blotting (cytoplasmic and cytoskeletal/nuclear-enriched fractions) and immunofluorescence in the androgen-responsive LNCaP and the non-responsive DU-145 and PC-3 cells, displaying a low, moderate and high aggressive phenotype, respectively. Targeted experiments were also conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 29 publications
(36 reference statements)
2
49
0
Order By: Relevance
“…eEF1A1 is a protein that triggers the initiation of protein translation elongation, and involved in the control of various cellular processes (16,18). Studies have shown that eEF1A1 is high expression in many tumors, and overexpression of eEF1A1 promotes cancer cell proliferation and cancer development (16,18). In this study, our data also found that eEF1A1 is upregulated in a variety of cancer cells, including HCC, breast cancer, colorectal cancer, pancreatic cancer, and cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…eEF1A1 is a protein that triggers the initiation of protein translation elongation, and involved in the control of various cellular processes (16,18). Studies have shown that eEF1A1 is high expression in many tumors, and overexpression of eEF1A1 promotes cancer cell proliferation and cancer development (16,18). In this study, our data also found that eEF1A1 is upregulated in a variety of cancer cells, including HCC, breast cancer, colorectal cancer, pancreatic cancer, and cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…To understand the molecular mechanism of tumor proliferation will contribute to the prevention and treatment of tumor (36,37). eEF1A1 is a protein that triggers the initiation of protein translation elongation, and involved in the control of various cellular processes (16,18). Studies have shown that eEF1A1 is high expression in many tumors, and overexpression of eEF1A1 promotes cancer cell proliferation and cancer development (16,18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas the molecular mechanisms contributing to carcinogenesis and progression of HCC still need to be fully clarified, many biological molecules have been proposed as relevant players. Some of them are mutually exclusive of neoplastic transformation as in the case of eukaryotic elongation factor 1 A2, a protein normally expressed only by skeletal muscle, heart and nervous system [2][3][4][5][6][7] . Thus, a better understanding of the mechanisms underlying these signaling cascades may be of great diagnostic and therapeutic potentials.…”
Section: Introductionmentioning
confidence: 99%
“…The eEF1A1 mRNA and protein are expressed ubiquitously in many cancer cell types (Joseph et al, 2004;Scaggiante et al, 2012) (supplementary material Fig. S4).…”
Section: Ink4amentioning
confidence: 99%